Implementasi Model Pembelajaran Kooperatif Tipe Jigsaw dalam Pembelajaran Matematika Ditinjau dari Kreativitas Berpikir Siswa - Hadi, Heri Sopian (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research was conducted to obtain an overview regarding the influence of the Jigsaw type cooperative learning model in mathematics learning in terms of students' creative thinking. The type of research used is experimentation with a quantitative approach. The sample in this study was taken using a saturated sampling technique with 25 students as an experimental class taught using the Jigsaw type cooperative learning model and 24 students as a control class taught using conventional learning. The instrument for collecting data is a questionnaire. The data normality test uses the Liliefors test and the homogeneity test uses Fisher. Hypothesis testing using the t test, shows tcount (2.73) > ttable (2.01) with ???? = 0.05 which states that ???????? is rejected, so it can be concluded that there is a significant influence on the Jigsaw type cooperative learning model in mathematics learning in terms of review. from students' creative thinking